Neonatal epignathus in the oral and pharyngeal regions: A case report. Issue 1 (27th March 2019) - Sugiyama, Madoka; Kanke, Kosuke; Suenaga, Hideyuki; Isojima, Tsuyoshi; Fujishiro, Jun; Hoshi, Kazuto
Abstract: Congenital teratoma that arises in the oropharyngeal region is called epignathus. Here, we report a case in which large epignathus extending from the pharynx to the oral cavity was resected. A female fetus was found to have a mass extending on her face to the pharyngeal region during a sonographic examination performed at 33 weeks' gestation. On the 9th day after birth, the tumor extending from the left nostril (10 cm) was excised by the pediatric surgeons. The residual tumor protruded from the oral cavity day by day. Pediatric and oral surgeons resected the tumor (14.5 cm). A bifid uvula was noted and submucosal cleft palate was suspected. No recurrence has been seen after 4 years' follow‐up.